The contributions of perceived competence, enjoyment, and fear of harm to movement confidence in older adults / Andrew M. Guilfoyle, Elizabeth A. Rose and Alastair K. Stewart - M. Guilfoyle, Andrew; A. Rose, Elizabeth (Faculty of Sports Science and Recreation, 2006)
The Movement Confidence Model proposes that perceptions of competence, enjoyment and fear of harm contribute to movement confidence. Participants (N = 54), male (n = 26) and female (n = 27), (aged from 50 to 65 years) completed a Movement Confidence Scale. Hierarchical regression revealed that perceived competence contributed to movement confidence. The contributions of enjoyment and fear of harm were marginal. In women perceived competence only contributed to movement confidence. Fear of harm and enjoyment did not contribute. For men all factors perceived competence, fear of harm and, enjoyment were important. Particular physical activities were linked to these gender differences. Future validation of the model to account for gender differences in perceived competence, enjoyment, fear of harm, and movement confidence, will assist its applicability in developing exercise programmes for older adults.